Macrolepidoptera of Chineta Nature Reserve (Altai Province, Southern Siberia, Russia) - Polina D. Pavlova (Acta Biologica Sibirica)
The article gives a faunal list of higher Lepidoptera, collected during May–August 2023 Chineta Reserve (Altai Province, Russia), which includes 343 species, eight of which are new to the fauna of the Altai Province: Manulea flavociliata (Lederer, 1853), Manulea pygmaeola (Doubleday, 1848), Eublemma amasina (Eversmann, 1842), Autophila asiatica (Staudinger, 1888) (Erebidae), Lacanobia mongolica Behounek, 1992, Hadena magnolii (Boisduval, 1829), Cerastis orientalis Boursin, 1948 (Noctuidae), and Scopula prouti Djakonov, 1935 (Geometridae). C. orientalis is a species with West-Siberian and Far-Eastern disjunctive areal.